Несколько штрихов к портрету А.И.Зайцева - Фролов , Э.Д. (Philologia Classica, 2007)
A memoir and considerations on scholarly and teaching activities of A. I. Zaicev (1927–2000), professor of classics at the University of St. Petersburg, by E. D. Frolov, professor of ancient history at the same university.